2018
DOI: 10.14419/ijet.v7i2.3.12625
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Mobile Robots Approach for Autistic Children Media Therapy

Abstract: Autism is neural development disorder which complex and is characterized by difficulties in social interaction, communication, emotion and limited behaviour, repetitive and stereotyped characters. The development of people with autism experienced a very significant increase. Autistic fine motoric development of children with autism is done through the hands by using tools or creative media such as brushes, pencils, paper, scissors, clay, plastisin, foam, and others. One way to improve fine motor in autistic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In other work-family conflict research, to determine the weight of the factors through identified based on lack of independence by used Fuzzy AHP and Fuzzy Type-2 DEMATEL have been applied [26]. Using tools as integrated algorithm in psychology and engineering approach also have been done by past studies [27], [28].…”
Section: Model Testingmentioning
confidence: 99%
“…In other work-family conflict research, to determine the weight of the factors through identified based on lack of independence by used Fuzzy AHP and Fuzzy Type-2 DEMATEL have been applied [26]. Using tools as integrated algorithm in psychology and engineering approach also have been done by past studies [27], [28].…”
Section: Model Testingmentioning
confidence: 99%